Confined-space annealing of 2D transition metal dichalcogenides: Improving properties, material reorganization, and chalcogen exchange - Christian Tessarek; Christian Petersen; Tim Grieb; Florian F. Krause; Alexander Karg; Christian Habben; Andreas Rosenauer; Martin Eickhoff (APL Materials)
Annealing can improve the structural quality of transition metal dichalcogenides grown by chemical vapor deposition, atomic layer deposition, and molecular beam epitaxy. However, decomposition and desorption of chalcogens from the layers limit process parameters, such as temperature and duration. In this study, it will be shown that using confined-space annealing, realized by close contact face-to-face sample arrangement, it is possible to extend this parameter range to higher temperatures and longer annealing times. The extended temperature range leads to significantly improved optical and structural quality of MoS2 and WS2 grown by atomic layer deposition. At temperatures above 1000 °C, a rearrangement of material leads to the formation of hexagonal structures, which are not present in as-grown samples. Confined-space annealing can also be used for conversion of MoS2 layers into ternary Mo(S,Se)2 and even binary MoSe2 using a proper Se containing reservoir. The confined space allows escape of organic precursor residuals but strongly reduces outdiffusion of S, resulting in an improved confinement of S in the interspace between the samples. Hence, no additional sulfur precursor is needed for annealing, leading to a simple, low-level technology process, which is non-toxic, environment friendly, and resource-efficient.